Lycopene Enhances the Beta Cell Capacity and Antihyperlipidemic Effects of Metformin on Type 2 Diabetic Rats - Nugroho, Heri; Sianturi, Medina; Retnoningrum, Dwi; Susiloningsih, Neni (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Hyperglycemia causes dyslipidemia in type 2 diabetes mellitus (T2DM). Metformin monotherapy is known to be less effective at improving glycemic status, insulin function, and lipid profiles. Lycopene is a potential antioxidant and has been shown to be hypoglycemic and hypocholesterolemic. However, the effects lycopene and metformin combination are still up for debate. This study was conducted to determine the potential of lycopene in enhancing the ability of metformin to improve glycemic status, insulin resistance, beta cell capacity, and lipid profile of T2DM rats.METHODS: Thirty male Wistar rats were randomly divided into six groups: control (N), T2DM-untreated (D), T2DM + metformin (DM), T2DM + metformin + 10 mg/kgBW lycopene (DMLy-10), T2DM + metformin + 20 mg/kgBW lycopene (DMLy-20), and T2DM + metformin + 40 mg/kgBW lycopene (DMLy-40). The treatment was administered once daily through oral route and lasted for 28 days, before blood samples were collected. Fasting blood glucose (FBG) was assessed by oxidase-peroxidase method, fasting serum insulin and HbA1c were measured using enzyme-linked immunosorbent assay (ELISA), while lipid profile was determined using enzymatic methods. The homeostatic model assessment for insulin resistance (Homa-IR) as well as the homeostatic model evaluation of β-cell function (Homa-B) were then calculated.RESULTS: Fasting serum insulin levels increased significantly (p<10.05) in the DMLy-20 and DMLy-40 groups, but Homa-B or high-density lipoprotein (HDL) did not significantly increase. Additionally, the FBG, HbA1c, Homa-IR, total cholesterol, triglyceride, and low-density lipoprotein levels were not significantly decreased than in the group treated with metformin alone.CONCLUSION: Lycopene can enhance the ability of metformin to improve the glycemic status, insulin resistance, beta-cell capacity, and lipid profile of T2DM rats.KEYWORDS: dyslipidemia, Homa-B, insulin resistance, lycopene, metformin, type 2 diabetes mellitus